2023
DOI: 10.1186/s40779-023-00461-z
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive look at the psychoneuroimmunoendocrinology of spinal cord injury and its progression: mechanisms and clinical opportunities

Abstract: Spinal cord injury (SCI) is a devastating and disabling medical condition generally caused by a traumatic event (primary injury). This initial trauma is accompanied by a set of biological mechanisms directed to ameliorate neural damage but also exacerbate initial damage (secondary injury). The alterations that occur in the spinal cord have not only local but also systemic consequences and virtually all organs and tissues of the body incur important changes after SCI, explaining the progression and detrimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 380 publications
1
8
0
Order By: Relevance
“…Similar conclusions can be drawn when evaluating the growing prevalence, incidence and burden of other neurological disorders, like Parkinson's disease, multiple sclerosis, epilepsy and spinal cord injury [24]. In the case of the latter, the low representation of this disease in tweets is especially striking, particularly due to the numerous psychosocial consequences for patients, relatives and healthcare professionals [32]. Thus, our results show great inequality on Twitter with respect to the consideration of different neurological diseases, with dementias being widely discussed and other entities, such as spinal cord injury, conspicuously ignored.…”
Section: Discussionsupporting
confidence: 55%
“…Similar conclusions can be drawn when evaluating the growing prevalence, incidence and burden of other neurological disorders, like Parkinson's disease, multiple sclerosis, epilepsy and spinal cord injury [24]. In the case of the latter, the low representation of this disease in tweets is especially striking, particularly due to the numerous psychosocial consequences for patients, relatives and healthcare professionals [32]. Thus, our results show great inequality on Twitter with respect to the consideration of different neurological diseases, with dementias being widely discussed and other entities, such as spinal cord injury, conspicuously ignored.…”
Section: Discussionsupporting
confidence: 55%
“…Taken together, these findings demonstrate that HSD consumption disrupts the balance of the gut microbiota and promotes disease development. Recent reports showed that gut microbiota dysregulation could be associated with low-grade inflammation and lots of pathological conditions by metabolites indirectly ( 50 , 51 ). Therefore, we analyzed the alteration of the metabolites in the stools of the mice.…”
Section: Discussionmentioning
confidence: 99%
“…Building on these pieces of evidence, we suggest that a research shift toward gut microbiome-mediated mechanisms would benefit interventional designs and offer personalized translational opportunities resulting in more efficacious management of anxiety symptomatology. We also want to draw attention to the importance of assuming an integrative perspective that takes into account the interconnectedness of multiple body’s systems, e.g., inflammatory, metabolic, nervous systems, analogously to what recently proposed for the clinical management of spinal cord injury patients ( 190 ). All these systems contribute to anxiety pathophysiology and should thus be accounted for when developing clinical treatments and during patients’ evaluation.…”
Section: Discussionmentioning
confidence: 99%